High level delegation from Ethiopia visits Nyando climate-smart villages - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 8 August 2014 The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), East Africa hosted an Ethiopian Government delegation at Nyando climate-smart villages, one of the program’s learning sites in East Africa. The delegation visited several farmers and saw how different innovations have been implemented in the CSV’s under a changing climate. The climate-smart innovations are helping smallholders in Nyando mitigate the impacts of climate change and also improve their incomes by improving productivity. The delegation came with an aim learning how the CSV approach works and replicating the same on a larger scale in Ethiopia. Photos J. Mango (ICRAF)